Supply Cain Risk Management - Goodwin, Les (2011)
“The management of supply chain risk is crucial to any business, more so to Rolls Royce who face an almost doubling of load within the next 10 years. So what is supply chain risk management and how well is it deployed within an operational business of Rolls Royce? What are the tools and techniques available and what are the key issues around implementing world class supply chain risk management with a Supply Chain Unit within Rolls Royce?”